Comparative structural insight into prefoldin subunints of archaea and eukaryotes with special emphasis on unexplored prefoldin of Plasmodium falciparum. Issue 8 (24th May 2022) - Kumar, Vikash; Behl, Ankita; Shoaib, Rumaisha; Abid, Mohammad; Shevtsov, Maxim; Singh, Shailja
Abstract: Prefoldin (PFD) is a heterohexameric molecular chaperone which bind unfolded proteins and subsequently deliver them to a group II chaperonin for correct folding. Although there is structural and functional information available for humans and archaea PFDs, their existence and functions in malaria parasite remains uncharacterized. In the present review, we have collected the available information on prefoldin family members of archaea and humans and attempted to analyze unexplored PFD subunits of Plasmodium falciparum ( Pf ). Our review enhances the understanding of probable functions, structure and mechanism of substrate binding of Pf prefoldin by comparing with the available information of its homologs in archaea and H. sapiens . Three Pf PFD out of six and a Pf prefoldin-like protein are reported to be essential for parasite survival that signifies their importance in malaria parasite biology. Transcriptome analyses suggest that Pf PFD subunits are up-regulated at the mRNA level during asexual and sexual stages of parasite life cycle. Our in silico analysis suggested several pivotal proteins like myosin E, cytoskeletal protein (tubulin), merozoite surface protein and ring exported protein 3 as their interacting partners. Based on structural information of archaeal and H. sapiens PFDs, P. falciparum counterparts have been modelled and key interface residues were identified that are critical for oligomerization of Pf PFD subunits. We collated information on PFD-substrate binding and PFD-chaperonin interaction in detail to understand the mechanism of substrate delivery in archaea and humans. Overall, our review enables readers to view the PFD family comprehensively. Communicated by Ramaswamy H. Sarma Abbreviations: HSP: Heat shock proteins; CCT: Chaperonin containing TCP-1; PFD: Prefoldin; PFLP: Prefoldin like protein; PfPFD: Plasmodium falciparum prefoldin; Pf: Plasmodium falciparum; H. sapiens: Homo sapiens; M. thermoautotrophicus: Methanobacterium thermoautotrophicus; P. horikoshii: Pyrococcus horikoshii